THU0543 A retrospective overview of the treatment modality, outcome and relapse risk of IGG4 related disease in hong kong: a dataset of 108 patients from four regional hospitals. (15th June 2017) - Tang, CP; Lee, KL; Lee, KW; Ng, WL; Wan, MC; Yuen, KY
Abstract : Background: Currently most consensus suggests treating IgG4 related disease (IgG4RD) with prednisolone 0.6mg/kg/day tapering over 6 months while some experts prefer continuation of steroid up to 3 years (1–3). Objectives: In this retrospective study, the treatment modality, response and relapse risk of IgG4RD patients over the past ten years from four regional hospitals in Hong Kong were analyzed. Methods: Four regional hospitals participated with study period from 1/1/2006 to 30/6/2016. Patients were diagnosed IgG4RD according to the Japanese Comprehensive Diagnostic Criteria for IgG4RD. Treatment response at 6 months was recorded as complete, partial or non-remission based on the patient's and physician's perspective. Relapse was defined as disease progression either clinically or radiologically. Statistical analysis: The association between treatment response and steroid dosage was analyzed by multivariate logistic regression. Risk factors for relapse were analyzed by multivariate cox regression and the hazard ratio was reported. Results: 37 cases had surgical excision and disease recurred in 5 cases (relapse rate =13.5%). 87 patients (81%) received steroid treatment. The mean starting prednisolone was 33.5mg daily, with a mean duration of 95.2 weeks. At 6 months, 5 patients (6%) had no response, 34 patients (41%) had partial remission and 44 patients (53%) had complete remission. 29 patients also received other immunosuppressants, including azathioprine (n=25), mycophenolate mofetil (MMF) (n=6), cyclosporine A (n=4), mercaptopurine (n=2) and rituximab (n=1). The overall response rate for azathioprine and MMF was 64% and 67% respectively. In the final multiple logistic regression, an initial prednisolone 30mg daily or above was associated with a higher complete remission at 6 months (OR=3.4, p=0.079) and the effect was more seen in patients with salivary and orbital involvement (OR=6.8, p=0.10) 18 patients relapsed after steroid was stopped and 6 patients relapsed while on prednisolone 2.5–7.5mg daily. The one year, two year and three year relapse rate were 13.3%, 24.1% and 26.5% respectively. In the final multivariate cox regression, the presence of maintenance steroid was associated with a lower relapse risk (Hazard ratio=0.121, p=0.000) while serum IgG4 level above twice upper limit of normal (Hazard ratio=5.283, p=0.029) and hepatobiliary involvement (Hazard ratio=2.164, p=0.095) were associated with a higher relapse risk. Conclusions: Most patients (94%) had good response to steroid. Patients with hepatobiliary involvement and serum IgG4 level above twice upper limit of normal were at higher relapse risk and a low dose, maintenance prednisolone for longer period is recommended. References: Kleger A, et al. IgG4-related autoimmune diseases: Polymorphous presentation complicates diagnosis and treatment. Deutsches Arzteblatt international. 2015;112(8):128–35. Ghazale A, et al. Immunoglobulin G4-associated cholangitis: clinical profile and response to therapy. Gastroenterology. 2008;134(3):706–15. Kamisawa T, et al. Standard steroid treatment for autoimmune pancreatitis. Gut. 2009;58(11):1504–7. Disclosure of Interest: None declared